Ecocity Elements in the Traditional Settlement of Kirtipur in Kathmandu Valley. (31st March 2016) - Singh, Sangeeta
Abstract: The increasing trend of urbanization has resulted in a growing imbalance in ecological systems that is affecting the lives of people globally. Planners often neglect the fact that human beings are part of the natural ecosystem and their ecological needs are ignored. Urban planning needs to focus on incorporating human–nature relationships as a key element. This paper explores ecocity elements in traditional towns of Kathmandu Valley with reference to Kirtipur, and seeks to argue that these consist of sustainable elements and practices that facilitate ecocity planning and development. An ecocity is quite a recent phenomenon. However, ecocity elements existed earlier and it seems relevant to include them in recent concepts. Similarities and differences of modern concepts and the lessons learnt from the traditional towns are worth exploring. Ecocity elements are analyzed in this paper by applying methods of document analysis, observations and interviews. Criteria for the analysis are ecologically oriented, sociocultural value oriented perspectives. The analysis will indicate if and how these elements/practices can be (a) maintained or (b) retrofitted or have to be (c) abandoned because they are not feasible anymore due to ecological, economic or sociocultural changes. Most of the traditional towns in the Kathmandu Valley were planned with the goal to maintain the natural ecosystem, and this has been reflected in the settlement pattern and land use, in the provision of basic infrastructure etc. The results of this paper indicate that there is a set of traditional sustainable elements and practices that are worth maintaining since they are part of the sociocultural and ecological tradition and that might contribute to ecocity transformation. Planning a city so as to disturb the natural ecosystem to the least possible extent is important for sustainability, and this research contributes to the theme of building sustainable and healthy cities. Copyright © 2016 John Wiley & Sons, Ltd and ERP Environment